Avaliação de argamassa geopolimérica à base de cinza volante - Lima, Lucas Pereira (2020)
The Pecém Thermoelectric Plant - UTE Pecém, is responsible for a significant energy generation in Brazil, generating tons of waste, including fly ash, where it has no specific purpose, standing out as a potential substitute for Portland cement. Geopolymeric mortars based on fly ash have several advantages, such as lower emission of pollutants, reuse of material, however, the mortar needs to present results that resemble conventional mortars. This study seeks to evaluate the geopolymeric mortar in the fresh and hardened state, with different proportions of activating solution / fly ash. For this purpose, three lines of geopolymeric mortar were made based on fly ash and a reference line composed of Portland cement for comparative purposes. The fly ash, originated from the Pecém Thermoelectric, was characterized by the XRay Fluorescence technique, laser particle size and specific gravity. Alkaline activators, sodium silicate and sodium hydroxide, as well as natural sand and Portland cement were used for the production of geopolymeric and conventional mortars. The samples produced were subjected to tests in the fresh state of consistency and plasticity and squeeze-flow. In the hardened state, tests of resistance to axial compression and tensile strength in flexion, specific mass, water absorption and voids index were performed, in addition to the visual analysis of efflorescence at 28 days. According to the results obtained, geopolymeric mortars, regardless of the activator / fly ash ratio, have good workability, with superior performance to that of the reference mortar. The squeeze-flow test demonstrated the greatest deformations, for the same load, obtained by geopolymeric mortars. The mortar with a higher activating solution / fly ash ratio (A3) showed better mechanical performance, obtaining a superior result, when compared to the reference mortar, by up to 145,87% in axial compression strength and 229,37% in tensile strength in flexion. The higher content of solids present in the activating solution and the lower content of additional water provided a lower void index, water absorption, influencing the presence of efflorescence on the faces of the specimens during the curing period.